2010
DOI: 10.1074/jbc.m110.174458
|View full text |Cite
|
Sign up to set email alerts
|

Chylomicron- and VLDL-derived Lipids Enter the Heart through Different Pathways

Abstract: Lipids circulate in the blood in association with plasma lipoproteins and enter the tissues either after hydrolysis or as non-hydrolyzable lipid esters. We studied cardiac lipids, lipoprotein lipid uptake, and gene expression in heart-specific lipoprotein lipase (LpL) knock-out (hLpL0), CD36 knock-out (Cd36 ؊/؊ ), and double knock-out (hLpL0/Cd36 ؊/؊ -DKO) mice. Loss of either LpL or CD36 led to a significant reduction in heart total fatty acyl-CoA (control, 99.5 ؎ 3.8; hLpL0, 36.2 ؎ 3.5; Cd36 ؊/؊ , 57.7 ؎ 5.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 66 publications
3
57
0
Order By: Relevance
“…We speculate that the LPL bridging function, supposedly still present only in the placenta of WT mice treated with P-407, could play a predominant role in the uptake of the whole nascent chylomicrons. In agreement with previous studies showing that steady state retinoid content of adult tissues was not different between WT and ML0 mice despite reduced chylomicron remnant uptake (15,17), steady state placental retinoid levels were not statistically different between WT and ML0 mice in our study (Table 2). Hence, in the absence of placental LPL expression, alternative pathways may exist to facilitate the uptake of postprandial retinoids by the placenta.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…We speculate that the LPL bridging function, supposedly still present only in the placenta of WT mice treated with P-407, could play a predominant role in the uptake of the whole nascent chylomicrons. In agreement with previous studies showing that steady state retinoid content of adult tissues was not different between WT and ML0 mice despite reduced chylomicron remnant uptake (15,17), steady state placental retinoid levels were not statistically different between WT and ML0 mice in our study (Table 2). Hence, in the absence of placental LPL expression, alternative pathways may exist to facilitate the uptake of postprandial retinoids by the placenta.…”
Section: Discussionsupporting
confidence: 82%
“…The fatty acid transporter, CD36, and the HDL receptor, scavenger receptor class B-1, are also expressed in human and mouse placenta (45)(46)(47)(48) and have been implicated in the uptake of lipoproteins. In agreement with Bharadwaj et al (17), who showed that the cardiac uptake of chylomicrons containing retinyl esters was not different from control in mice lacking CD36, we found no difference in CD36 mRNA expression levels between ML0 and WT mice regardless of the dietary regimen. We show that only when ML0 were fed the vitamin A-excess diet, scavenger receptor class B-1 expression was up-regulated in placenta (Fig.…”
Section: Additional Mediators Of Lpl Action At the Maternal-fetalsupporting
confidence: 81%
See 2 more Smart Citations
“…Other potential sources for free fatty acids are lipolysis of circulating lipoproteins by lipoprotein lipase, hydrolysis of intramyocardial triglyceride by adipose triglyceride lipase, and uptake of lipids via very low-density lipoprotein receptors. [20][21][22] In this context, it is interesting that the expression of both sterol-regulatory element-binding protein-1c and peroxisome proliferator activated receptor-γ were reported to be increased in heart biopsies of subjects with the MetS, reflecting adaptation to metabolic derangements. 23 Recently, dynamic positron emission tomographic imaging of both heart and liver was used to follow-up the fate of dietary fatty acids in humans.…”
Section: Discussionmentioning
confidence: 99%